The influence and lag-effect of temperature and precipitation on the incidence and mortality of tuberculosis, 2000–2021: an observational study - Liu, Qiao; Wang, Yaping; Liu, Min; Zhao, Yanlin; Liu, Jue (Frontiers in Public Health, 2025)
BackgroundTuberculosis (TB) remains a major global health concern, particularly in low-and middle-income countries. Climate change may influence TB burden through effects on human health, living conditions, and pathogen transmission, yet its long-term impact remains underexplored.MethodsThis observational study integrated data on temperature and precipitation obtained from NCEI/NOAA, TB burden from the Global Burden of Disease Study 2021, and socio-economic covariates from the World Bank open data platform. We used quasi-Poisson regression to assess non-lagged associations and applied distributed lag non-linear models to estimate lagged effects of climate exposure on age-standardized incidence and mortality rates (ASIR and ASMR) of TB from 2000 to 2021.ResultsFrom 2000 to 2021, global TB age-standardized incidence rate and age-standardized mortality rate declined annually by 2.15 and 4.18%, respectively, with higher burdens in Africa and Southeast Asia. TB rates were elevated in males and those over 50, while younger age groups (<5, 5–14) in countries like the Philippines and Zimbabwe saw increases. A 1°C rise in temperature reduced age-standardized incidence rate by 0.89% and ASMR by 1.61%, while 1 mm increased precipitation raised age-standardized mortality rate by 1.80%, impacting males more. Higher temperatures increased TB rates in South-East Asia and Western Pacific, while precipitation raised rates in Africa, Eastern Mediterranean, and the Americas. Low and high temperatures showed negative lag effects after 12–15 years, while high temperatures posed a short-term risk for those aged 50+. 0 mm precipitation was protective after 10–15 years, while intermediate and humid precipitation levels had mixed effects, including some negative impacts on mortality.ConclusionThere is urgent need for tailored interventions that strengthen healthcare infrastructure, enhance disaster preparedness, and address both social determinants and climatic influences. By incorporating climate factors into the understanding of TB trends, our study offers critical insights to guide public health strategies in the era of climate change, contributing to more effective approaches for achieving the SDG targets for TB elimination.